A Coalition-Formation Approach to Equilibrium Federations and Trading Blocs - Burbidge, John B.; DePater, James A.; Myers, Gordon M.; Sengupta, Abhijit (American Economic Review, 1997)
We develop a model in which states may choose to form coalitions to capture efficiency gains from policy coordination. Joining a coalition entails setting the policy variable to maximize the coalition's aggregate payoff at a Nash equilibrium against nonmembers, and to commit to a transfer scheme to share the gains. With two states, the unique equilibrium structure is complete federation; with more than two states, incomplete federation can be the unique equilibrium. Interpreting this result in terms of customs unions, the trend to trading-bloc formation may be equilibrium behavior even with cooperation and transfers within customs unions.